2014
DOI: 10.1590/1983-1447.2014.03.45187
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices for the prevention of diabetic foot

Abstract: The purpose of this study was to identify the knowledge, attitudes and practices for the prevention of diabetic foot in patients with diabetes mellitus type 2. This study was based on a cross-sectional survey conducted in two Family Health Units, in the city of Picos - PI, Brazil, with 85 diabetics of both sexes, by means of a semi-structured Knowledge, Attitude and Practice questionnaire. There was a predominance of females in the study (62.4%). On the topic of foot care, 49.4% had no knowledge on hygiene or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 9 publications
4
20
0
9
Order By: Relevance
“…The study showed that most of patient's responses to preventive foot care practices were satisfactory especially in (self-foot care, daily foot washing, ensuring that shoe size before buying it). The proportions of these positive practicing responses were high, whereas majority of them reported that they personally depending on theirselves to caring foot, this positive practice has shown in other studies (9,21). Majority of diabetic patients reported that they always practicing foot washing daily, and this important practice has come in accordance with other studies (4, 8).…”
Section: Discussionsupporting
confidence: 82%
“…The study showed that most of patient's responses to preventive foot care practices were satisfactory especially in (self-foot care, daily foot washing, ensuring that shoe size before buying it). The proportions of these positive practicing responses were high, whereas majority of them reported that they personally depending on theirselves to caring foot, this positive practice has shown in other studies (9,21). Majority of diabetic patients reported that they always practicing foot washing daily, and this important practice has come in accordance with other studies (4, 8).…”
Section: Discussionsupporting
confidence: 82%
“…Levels of knowledge in the present study were in the low to average range, and self-care practices were inadequate or moderately inadequate. These findings coincide with other investigations that pointed out significant deficits in levels of knowledge, in addition to self-care practices that were either not performed or were incomplete (10,13,18) . These results are striking and lead one to reconsider whether the intervention strategies used for people with DM and their caregivers are effective for achieving the necessary and pertinent changes in the care behavior of this group of people.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, knowledge is conducive to proper foot care, whereas lack of knowledge and/or clear daily foot care plans increases the risk of developing ulcers and amputations (9) . It also leads to inadequate practices and confirms the thesis that even diabetics with proper attitudes are unable to perform correct self-care practices (10) . This indicates that the foot care knowledge and practices of patients are highly associated (11) .…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…This is because it commonly occurs in DM and has great possibilities of incapacitating the individual, thus causing loss of thermal, painful and tactile sensitivity as a result of blood glucose decompensation. 26 There were limitations in the study, such as the repetition of users during the months following the data collection for the quarterly return and the reduction of the sample size in the glycemic control variable in the last visit, because this datum was not recorded. The contributions were diverse, such as the health education process by means of meetings with the team and patients with diabetes in which we clarified the main pieces of doubt found regarding foot care, alterations that should be a reason for warning of major complications, prevention of ulcers and amputations.…”
Section: /13mentioning
confidence: 99%